Factors Affecting Couples of Reproductive Age (CRA) Without Using Contraception - Siregar, Rahmah Juliani; Maryam Latifah Harahap; Elvi Suryani; Dewi Aminasty Siregar; Fatimah (International Journal of Public Health Excellence (IJPHE), 2022)
Acceptor Family Planning (KB) is Couple Age Fertile (EFA) who use wrong one tools / drugs contraception . Although the family planning program has been declared quite successful in Indonesia, in its implementation so far there are still obstacles that are felt, among others, that there are still many couples of childbearing age (PUS) who are still not participants in family planning. Population in study this is couple age fertile who are not use tool contraception in Village Sigulang District Southeast Padangsidimpuan Year 2022 as many 25 PUS. It is hoped that health workers will held more counselling enterprising again so motivating respondents who have knowledgeable good for want to use tool contraception.